Alkali-Silica Reaction, ASR – Review on how to deal with ASR in concrete structures - Custódio, J. (2015)
A significant number of problems related to concrete deterioration have been detected in large concrete structures in Portugal and worldwide, the leading cause being ASR. The importance of these structures, the number of for which ASR has already been identified or is very likely to be diagnosed in a near future, as well as the number of structures that are under or planned for construction, which may also come to develop ASR is why it is still nowadays a major concern and a complex problem. Therefore, a study is being conducted at LNEC to diminish the negative impact of ASR by increasing knowledge on how to reliably control ASR in new structures and on how to properly assess its extent and potential for future development in the existing ones, so that the risks to structural integrity and need for mitigation/remediation actions can be properly assessed. This paper presents methodologies, based on state-of-the-knowledge collected on that study, which may be used by construction industry stakeholders in the prevention of ASR in new concrete structures and on ASR diagnosis and prognosis in existing concrete structures.